Artificial Intelligence and Political Campaign on Indonesian Presidential Election 2024 - R. Yogie Prawira; Asy'ari; Akhmad Roqi Alawi (DAWUH : Islamic Communication Journal, 2026)
The rise of AI has significantly transformed the political landscape and process, presenting a dichotomy that can facilitate and jeopardize the electoral process. This study qualitatively explored the emergence of AI in political campaigns during the Indonesian Presidential Election 2024. Using digital ethnography, including interviews with social media users and partisans of diverse profiles, as well as offline and online content analysis observations of GenAI campaign material, this article discusses the Indonesian political landscape, AI use in campaigns to construct new identities, and reflections on digital democracy in Indonesia. AI use by presidential candidates has shaped identities and led to different public responses between text-based and image-based GenAI. Support and rejection are forms of public participation facilitated by digital media. Digital activism #TolakGambarAI (#RejectAIImage) encourages specific regulations for AI use in election campaigns. Advancements in AI and digital media present future democratic challenges to realize a healthy and fair democratic culture.